Thermodynamic, Adsorption and Corrosion Inhibition Studies of Mild Steel by Artemisia vulgaris Extract from Methanol as Green Corrosion Inhibitor in Acid Medium - Karki, Nabin; Choudhary, Yogesh; Yadav, Amar Prasad (Journal of Nepal Chemical Society, 2018)
Available with full text.